Aspidistra globosa (Asparagaceae, Nolinoideae), a new species with erect stem from southern Vietnam - Vislobokov, Nikolay A.; Nuraliev, Maxim S.; Kuznetsov, Andrey N.; Kuznetsova, Svetlana P. (Phytotaxa, 2016)
Aspidistra globosa is described and illustrated as a new species from southern Vietnam (Gia Lai province, Kon Ka Kinh National Park). The new species has long erect stem, which is a rare feature in the genus Aspidistra. Aspidistra globosa resembles A. khangii and A. locii in globoid perigone and erect stem, but differs in smaller flowers, color of perigone, position of anthers and orientation of flower.